Assessment of Prescription Errors Related to Antimicrobials - A Prospective Study - N. A. KHAN; M. ABID; A. PATRA (International Journal of Pharma and Bio Sciences, 2010)
Prescription errors related to use of Antimicrobial agents (AMAs) basing on Patient’s demographics viz. age & sex and a database was constructed for such awareness program. From 150 prescriptions, the error regarding prescription of antimicrobial agents without hypersensitivity test or diagnosis of specific parasite male patients shown a higher proportion (92%) followed by the female patients (87.8%). The data revealed that such errors were almost in a similar proportion in the male patients and female patients (51.3% and 51.2% respectively). Unauthorized synergistic combinations of antimicrobial agents with low therapeutic index were greater in male patients (20.27%) than in female patients (14.63%). Prescribing mistakes need to be acknowledged, taken seriously, discussed openly, and actions taken in a blame free culture. Pharmacists’ collusion in the current low profile of prescribing mistakes, giving verbal feedback to the prescriber, or writing on sticky notes must be stopped